A rare case of TB cervix-cause of secondary amenorrhoea and primary infertility: case report - Thomas, Julie; Peter, Monalisa; Srikonda, Yashaswini (International Journal of Research in Medical Sciences, 2018)
A 23 years old female presented with chief complaints of 11/2 years of primary infertility and postcoital bleeding for 7 months. On examination cervix was unhealthy and was bleeding on touch. A provisional diagnosis of chronic cervicitis was made. However, histopathology of the cervical biopsy revealed granulomatous lesion suggestive of tuberculosis. The patient responded to anti-tuberculosis therapy. In a young patient, with suspicious cervical lesion and history of contact bleeding, a benign pathology like cervical tuberculosis is extremely low. The outlook is good with full recovery, if the treatment is carried out properly and promptly.